AB0615 Favorable response to belimumab seen at three months. (23rd January 2014) - Shum, K.; Buyon, J.; Franks, A.; Furie, R.; Kamen, D.; Manzi, S.; Petri, M.; Ramsey-Goldman, R.; Tseng, C.-E.; Wallace, D.; van Vollenhoven, R.; Askanase, A.
Abstract : Background: Belimumab (Benlysta) is a monoclonal antibody that inhibits soluble B-Lymphocyte Stimulator and improves SLE disease activity. Objectives: This study was initiated to evaluate the use of Belimumab in academic SLE clinical practices. Methods: An invitation to participate was sent to 16 physicians experienced in SLE Phase III clinical trials. All agreeing to participate completed a one page questionnaire for each patient prescribed Belimumab. The questionnaire contained demographic information on each patient (age, gender, race/ethnicity), SLE data (duration of disease, SELENA-SLEDAI, clinical manifestation(s) targeted, background medications), and Belimumab information (start date, clinical response, side effects). Clinical response was defined as the investigator's impression of a ≥50% improvement in the initial manifestation being treated and no worsening in other organ systems. Results: Of 16 invitations sent, ten investigators accepted to participate in the study. Questionnaires on 68 treated patients were returned. The mean age was 44.8±11.3 years old, 92.6% were female, 73.5% White, 16.2% Black, 7.4% Asian, and 7.4% Hispanic. The average SLE disease duration was 11.1±8.7 years. All patients were ANA positive. Concomitant medications included: antimalarials in 69.1%, immunosuppressants in 72.0% (Azathioprine 19.1%, Mycophenolate Mofetil 38.2%, Methotrexate 14.7%), and prednisone in 61.8% (average dose of 10.9±11.9 mg, 59.5% on ≥10 mg). Only 2.9% of patients were not on background SLE medications. The dominant clinical manifestation driving treatment was arthritis (77.9%) followed by rash (42.6%) and serositis (19.1%). Other SLE manifestations present included renal (7.4%, 4/5 membranous, 1/5 proliferative) and hematological (8.8%). Approximately half of patients (45.6%) had two or more active manifestations. Twenty-three patients were on Benlysta for at least 3 months. Of those, 17 patients had clinical response observed by 3 months with improvements in arthritis and rash. Conclusions: These early data support the use of Benlysta across all ethnic groups and efficacy similar to that reported in the Phase III trials. Relevant to physician and patient expectations, improvement was observed within 3 months. Disclosure of Interest: None Declared